2021
DOI: 10.3390/su132011330
|View full text |Cite
|
Sign up to set email alerts
|

Parking Policy as a Tool of Sustainable Mobility-Parking Standards in Poland vs. European Experiences

Abstract: Contemporary cities generally lack the balance between the development of the spatial structure and the communication possibilities of the inhabitants. The high motorisation rate in Poland, as well as in other European countries, and the preferred choice of individual means of transportation have both contributed to a significant increase in congestion over the last 10 years. The aim of this research was to try to establish to what extent a consciously conducted parking policy can help control the mobility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The parking policy [17] for residential areas in Poland follows the popular system in Europe of defining minimum parking indicators for individual areas. According to this concept, residential areas are self-sufficient and balance their needs on their own land.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parking policy [17] for residential areas in Poland follows the popular system in Europe of defining minimum parking indicators for individual areas. According to this concept, residential areas are self-sufficient and balance their needs on their own land.…”
Section: Discussionmentioning
confidence: 99%
“…In many countries, including Poland, planning regulations require a defined number of parking spaces to be provided. There are examples in the literature where this requirement has been removed or modified [17][18][19]. Minimum parking requirements are often criticised for creating excess parking, degrading urban form, reducing housing affordability, and promoting car dependency [19,20].…”
Section: Parking Issues In Residential Areasmentioning
confidence: 99%
“…The development of sustainable mobility will generate travel as a derived demand and travel cost minimization [31,32]. The parking supply is far from perfectly elastic [33].…”
Section: Parking Price Controlsmentioning
confidence: 99%
“…Many researchers deal with the problem of sustainable parking. While looking into the problem, the authors of [55] analyzed the high motorization rate in Poland and other European countries, and they found that the preferred choice of individual means of transportation hascontributed to a significant increase in congestion over the last ten years. In their results, the authors analyzed almost 550 planning documents from the years 2000-2019 and parking standards operating in individual countries and established that for 20 years, Polish cities have mainly been exploring the possibility of determining the minimum rate of parking spaces.…”
Section: Research Gapsmentioning
confidence: 99%